2021
DOI: 10.1186/s12863-021-00993-0
|View full text |Cite
|
Sign up to set email alerts
|

Brain areas involved with obsessive-compulsive disorder present different DNA methylation modulation

Abstract: Background Obsessive-compulsive disorder (OCD) is characterized by intrusive thoughts and repetitive actions, that presents the involvement of the cortico-striatal areas. The contribution of environmental risk factors to OCD development suggests that epigenetic mechanisms may contribute to its pathophysiology. DNA methylation changes and gene expression were evaluated in post-mortem brain tissues of the cortical (anterior cingulate gyrus and orbitofrontal cortex) and ventral striatum (nucleus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…It was thus suggested that there might be different biological processes specific to each striatum region, each contributing in various ways to OCD pathophysiology. Another study from the same research group subsequently focused on DNA methylation (DNAm) changes and gene expression in post-mortem brain tissues of the cortical (anterior cingulate gyrus and OFC) and ventral striatum (PT, CN, and NAC) areas from a slightly larger cohort of eight OCD patients and eight matched healthy controls [ 97 ]. Their investigation was in response to studies on DNAm in substitute peripheral tissues, such as blood [ 98 - 100 ], including mononuclear cells [ 101 ] and saliva [ 102 ], and involved consideration of the methylation clock in brain tissues from patients with OCD as a complement of tissue senescence, associated with physiological ageing [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was thus suggested that there might be different biological processes specific to each striatum region, each contributing in various ways to OCD pathophysiology. Another study from the same research group subsequently focused on DNA methylation (DNAm) changes and gene expression in post-mortem brain tissues of the cortical (anterior cingulate gyrus and OFC) and ventral striatum (PT, CN, and NAC) areas from a slightly larger cohort of eight OCD patients and eight matched healthy controls [ 97 ]. Their investigation was in response to studies on DNAm in substitute peripheral tissues, such as blood [ 98 - 100 ], including mononuclear cells [ 101 ] and saliva [ 102 ], and involved consideration of the methylation clock in brain tissues from patients with OCD as a complement of tissue senescence, associated with physiological ageing [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…An additional analysis using the Blood Brain DNA Methylation Comparison Tool [ 26 ] allowing for the interrogation of specific brain regions, i.e., the prefrontal cortex, the entorhinal cortex, the superior temporal gyrus and the cerebellum, revealed substantial blood–brain methylation correlations for CpGs cg15890734 and cg01070250. Still, none of the online available databases contains information on brain areas relevant for OCD such as the anterior cingulate gyrus, orbitofrontal cortex, ventral striatum, nucleus accumbens, caudate nucleus and putamen [ 41 ] and thus do not allow for a conclusive analysis. Given that no gene expression data was available, interpretation of the biological consequences of the observed differences in DNA methylation on gene transcription is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The role of STAT3 in mood disorders has been indicated by several lines of evidence in terms of STAT3 activity, serotonergic neurotransmission, and the control of behaviors relevant to psychopathology [ 32 ]; however, evidence for STAT3 in the course of OCD is still limited. A recent bioinformatic study by de Oliveira et al predicted STAT3 as a significant transcription factor in relation to OCD [ 33 ]. We also predicted four miRNAs, such as miR-21-5p, miR-32-3p, miR-347a-3p, and miR-590-5p, for the STAT3 gene.…”
Section: Discussionmentioning
confidence: 99%